Change of Safe Needling Depth at Acupoint GB21 according to Posture and Breathing. (8th January 2018) - Chu, Hongmin; Kim, Jaehyun; Ha, Wonbae; Cho, Eunbyul; Kang, Geon; Park, Seongjun; Jang, Jongwon; Yang, Seung Bum; Kang, Yeonseok; Lee, Sanghun; Kim, Jae-Hyo
Abstract : Acupoint GB21 (Jianjing) is used for treating back and shoulder pain but is associated with a risk of pneumothorax. We aimed to determine the SND (safe needling depth) at GB21 according to posture and breathing in real time. Ultrasonographic images of GB21 during normal breathing, inspiration, and expiration in a SP (sitting position) were acquired for 52 healthy volunteers. Images were also acquired during normal respiration in the PP (prone position) with arms raised and lowered. The average SND was greater for men than for women (p < 0.05 ). Analysis of variance revealed that the SND was greater for the PP than for the SP (p = 0.0 1 and p < 0.05, resp.). Although the SND tended to change according to posture, the average depth tended to deviate widely in some subjects. During breathing, the differences between inspiration and expiration were less than 1 mm in most subjects, but some showed differences more than 4.5 mm. The SND at GB21 was greater in overweight subjects and significantly greater in the PP and during maximal expiration. However, intragroup differences were greater than the intergroup differences. Therefore, it is dangerous to simply apply needling depth on a gender or BMI basis. The practitioner would adjust the SND by examining the individual anatomical structures.